Creativity in Education International Perspectives - Brown, Nicole; Ince, Amanda; Ramlackhan, Karen (UCL Press, 2024)
Creativity has become a buzzword across all disciplines in education and across all phases, from early years through to tertiary education. Although the meaning of creativity can change vastly depending on the global educational setting, it is impossible to ignore the applicability and relevance of creativity as an educational tool, philosophical framework and pedagogical approach. Through case studies of creativity in varying settings and diverse contexts, this collection explores the ground-breaking work undertaken internationally to support, develop and future-proof learners with, and for, creativity. The chapters are centred around a practice based enquiry or other forms of empirical research. This provides the scholarly basis upon which creativity is continuously reconceptualised and redefined in the educational and country-specific context of each study. Contributors from different countries then provide critical, reflective and analytical responses to each chapter. These conversational responses focus further on international education perspectives and provide a dialogue for educators into how methods and approaches can be transferred, translated and contextually mediated for different environments. Through the case studies and responses, Creativity in Education provides practical insights for application in a wide range of educational settings and contexts, such as the use of art exhibitions and object-work, as well as more philosophical approaches to teacher education, leadership for learning and creativity as a universal phenomenon.